Detailed study on the thermal, photo-physical and electrochemical properties and OFET applications of D-pi-A-pi-D structured unsymmetrical diketopyrrolopyrrole materials - Bharath, D.; Chithiravel, Sundaresan; Sasikumar, M.; Chereddy, Narendra Reddy; Shanigaram, Balaiah; Bhanuprakash, K.; Krishnamoorthy, K.; Rao, V. Jayathirtha (RSC Advances, 2015)
A series of seven unsymmetrical diketopyrrolopyrrole (DPP) derivatives with donor-pi-acceptor-pi-donor (D-pi-A-pi-D) architecture have been designed, synthesized and well characterised. The effect of the electron donating capacity and extent of electronic conjugation of the end-capping units on the thermal, photo-physical and electrochemical properties of the synthesized materials was thoroughly investigated using various experimental techniques and theoretical calculations. Organic field-effect transistors (OFETs) were fabricated using these materials to obtain their hole/electron transporting characteristics. All these materials showed moderate to good hole transporting ability, and the OFET fabricated using the DPP-derivative with benzofuran and pyrene end groups exhibited a hole mobility of 6.7 x 10(-4) cm(2) V-1 s(-1) with VT of similar to 9 V. The observed photo-physical, electrochemical, thermal, and charge carrier properties of the synthesized DPP-derivatives indicated their applicability in various areas like organic photovoltaics, disposable electronics and biomedical devices.